Hydroseeding tackifiers and dryland moss restoration potential. (28th July 2019) - Blankenship, W. Dillon; Condon, Lea A.; Pyke, David A.
Abstract : Tackifiers are long‐chain carbon compounds used for soil stabilization and hydroseeding and could provide a vehicle for biological soil crust restoration. We examined the sensitivity of two dryland mosses, Bryum argenteum and Syntrichia ruralis, to three common tackifiers—guar, psyllium, and polyacrylamide (PAM)—at 0.5×, 1.0×, and 2.0× of recommended (×) concentrations for erosion control and revegetation. We measured moss shoot, gemma, and protonema production as well as moss organic matter and bound sand masses as indicators of growth and soil holding ability. We tested sand and tackifier chemistry to investigate potential nutrient and toxicant potential on moss growth. Groups of 10 fragments from field‐collected mosses were grown on sand in open petri dishes arranged in a growth chamber in replicated blocks containing each tackifier and concentration combination plus a distilled water control. Bryum ( n  = 10) and Syntrichia ( n  = 9) growth were measured at the end of 6 and 5 weeks, respectively. Overall model tests yielded statistically significant results ( p  < 0.001) for every variable in each species. When compared to water, guar tended to decrease growth, psyllium tended to increase growth, and PAM's effects were generally neutral to positive. Within tackifier types, increasing concentrations of guar tended to decrease growth, while increasing concentrations of psyllium tended to increase growth. Changes in PAM concentrations had little effect on growth. Increases in guar and psyllium lowered pH and increased P and K. Psyllium and PAM yielded promising results as potential agents of dispersal and adherence of dryland mosses in field restoration.